Determination of the optimal location and the number of sensors for efficient heating, ventilation, and air conditioning system operation in a mechanically ventilated pig house. (May 2023) - Yeo, Uk-Hyeon; Lee, Sang-Yeon; Park, Se-Jun; Kim, Jun-Gyu; Jeong, Deuk-Young; Decano-Valentin, Cristina S.; Kim, Rack-Woo; Lee, In-Bok
Abstract : Monitoring inside pig houses for environmental control is usually conducted using either a single or a small number of sensors. It is therefore difficult to monitor the representative rearing environment and provide appropriate control strategies. It is necessary to determine proper monitoring locations to precisely monitor and then control the environment inside pig houses. Thus, this study aimed to identify the appropriate sensor location according to the number of installed sensors that can represent the entire environment inside a pig house and detect the locations where internal changes occurs that are greatly affected by the external environment. Optimal locations for each number of sensors were assessed by the application of an error-based method (EBM) to select monitoring locations that can represent the entire environment of the pig house and an information-entropy-based method (IEBM) to select monitoring locations with significant environmental changes. When selecting air temperature monitoring locations with the EBM during the entire experimental period, the middle sensor installed along the corridor (P-10) indicated the air temperature similar to the average air temperature of all sensors installed inside the pig house. Root mean square error (RMSE) and mean absolute percentage error (MAPE) of the P-10 location showed errors of 0.9 °C and 2.9%, respectively. With the installation of three sensors, accurate air temperature monitoring was possible within MAPE of 1%. The sensor location selected with the IEBM was near the pig house entrance (P-16). The sensor location showed errors of 2.5 °C and 13% for RMSE and MAPE, respectively. Highlights: Optimal sensor locations were evaluated for environmental measurement in a pig house. There was a difference between the existing and the optimal sensor locations. The optimal sensor location was determined according to the number of sensors. The optimal number of sensors to be installed in the pig house was determined.